High‐strength/high‐modulus polyvinyl alcohol fiber reinforced poly(amino acid)/hydroxyapatite composite for load‐bearing orthopedics applications. Issue 4 (14th February 2023) - Wu, Yanan; Lyu, Defu; Chen, Lichao; Ren, Haohao; Yan, Yonggang
Abstract: Bone defects in the load‐bearing area require bone reconstruction using strong biomaterial with mechanical properties like cortical bone. Herein, the high‐strength/high‐modulus polyvinyl alcohol fiber (PVA) was first designed to incorporate into poly(amino acid) (PAA)/hydroxyapatite (HA) to obtain a new poly(amino acid)/hydroxyapatite/polyvinyl alcohol fiber (PAA/HA/PVA) composite via a melt extrusion process. To improve the interfacial adhesive performance, the titanate coupling agent HY‐109 [isopropyl tris(dodecylbenzenesulfonyl) titanate] was used for simultaneously graft modification of the PVA fiber and HA (TPVA, THA). The effect of their components on the mechanical properties and degradation ability were investigated by electromechanical universal testing machine and in vitro phosphate buffer solution soaking. The results indicated that the PAA/30THA/20TPVA composite had the most ideal mechanical and degradation properties, which far exceed those of PAA and PAA/THA composite. In addition, in vitro simulated body fluid immersion and cell culture experiment showed the PAA/THA/TPVA composites boosted in vitro bioactivity and exhibited excellent cytocompatibility and osteogenic activity in cell attachment, proliferation, alkaline phosphatase activity, matrix mineralization, and osteogenesis‐related gene expression. These reports demonstrated that the developed PAA/THA/TPVA composite displayed comprehensive performance optimizations, which showed its potential as a novel biomaterial to be applied as load‐bearing implant in the field of orthopedics. Abstract :